Misrepresentation Of Islam In Islamic Films: Analysis Of Key Incidents Of The Message (1977) - Osama Kanaker; Rosidayu Sabran; Suria Hani A. Rahman; Salah Mohamed Zaki Ibrahim (Universiti Sains Islam Malaysia, 2024)
Film is a medium that depicts human activities. It visually portrays ideology and culture as well as empowers knowledge and the understanding of civilisation. The most concern is about the misrepresentation of media content, particularly concerning Islam and Muslims in films. The Message (1977, dir. Moustapha al-Akkad) is one of many made-in–Hollywood films that portray Islam and Muslims livelihood in Mecca during the revelation era of Prophet Muhammad (PBUH), and His migration from Mecca to Madinah. This paper intends to focus on how Islam is being represented in this film and how it portrays Prophet Muhammad (PBUH) and his companions. The main question that this paper attempts to answer is: are the actions and incidents of The Message film authentically portrayed? Identification of scenes containing actions and key incidents were done through the lens of content analysis. Based on the analysis of key incidents, findings indicate that the film supports the propaganda against Islam that Islam is a terrorist religion and Muslims are aggressors.